Blockholder monitoring and the efficiency of pay-performance benchmarking - Kim, Kyonghee (Journal of Corporate Finance, 2010)
In this article I examine how the performance sensitivity of CEO compensation is related to the level and turnover of outside block ownership. Separating firm performance into firm-specific (Skill) and exogenous (Luck) components, I find that pay sensitivity to Luck increases with blockholder turnover, whereas pay sensitivity to Skill increases with blockholding size. Furthermore, when blockholder turnover is higher, CEO pay increases more with positive Luck but does not decrease as much with negative Luck; also, excess CEO compensation is larger. Thus, the rent accruing to CEOs via asymmetric pay sensitivity to Luck is partly explained by short investment horizons of large shareholders.